152 SURGICAL PROCEDURE AND OUTCOME OF MEDIASTINOSCOPIC RADICAL ESOPHAGECTOMY FOR ESOPHAGOGASTRIC JUNCTION CANCER. (17th September 2021) - Shiozaki, Atsushi; Fujiwara, Hitoshi; Konishi, Hirotaka; Kudou, Michihiro; Shimizu, Hiroki; Arita, Tomohiro; Kosuga, Toshiyuki; Morimura, Ryo; Kuriu, Yoshiaki; Ikoma, Hisashi; Kubota, Takeshi; Okamoto, Kazuma; et al.
Abstract: : We started performing mediastinal lymph node dissection by a laparoscopic transhiatal approach (LTHA) in 2009. To date, 371 patients had undergone our method during various esophageal surgical procedures, including esophagogastric junction cancer (EGJC). Furthermore, we started performing single-port mediastinoscopic cervical approach in 2014, and developed a simple technique for transmediastinal radical esophagectomy (TMr) without thoracic approach (258 cases). Forty patients with EGJC were also treated by TMr. Methods: Left single-port mediastinoscopic cervical approach was performed with pneumomediastinum. Mainly for advanced SCC, upper mediastinal lymph node dissection including recurrent laryngeal nerve LNs was performed with intraoperative monitoring using NIM system. Next, LTHA was performed for en bloc mediastinal lymph node dissection. The esophageal hiatus was opened, and working space was secured by Long Retractors. The posterior plane of the pericardium was extended. The posterior side of LNs was then separated. Finally, while lifting LNs like a membrane, they were resected from bilateral mediastinal pleura. Reconstruction with narrow gastric conduit was performed through substernal tract. Results: Patients with EGJC performed TMr were analyzed (n = 40, SCC/Adeno/Others = 21/17/2). Upper mediastinal lymph node metastasis was found in 6 cases (SCC/Adeno = 3/3), middle mediastinal lymph node metastasis was found in 2 cases (SCC/Adeno = 1/1), and all of them had advanced tumors. Their perioperative outcome were compared with those performed the right thoracotomy (n = 41). The operative time and bleeding were decreased by TMr. The number of resected mediastinal lymph nodes, pR0 rate, and mediastinal recurrence in the two groups were not different. In 95.0% of patients treated by TMr, extubation was performed at 0 POD. Postoperative respiratory complications was decreased by TMr (TMr:7.5%, thoracotomy:17.1%). Conclusion: This procedure, TMr, resulted in a good surgical view, safe en-bloc mediastinal lymph node dissection, and the decrease of postoperative respiratory complications in patients with EGJC.